2021
DOI: 10.1016/j.jbc.2021.100854
|View full text |Cite
|
Sign up to set email alerts
|

Protein haploinsufficiency drivers identify MYBPC3 variants that cause hypertrophic cardiomyopathy

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 88 publications
2
38
0
Order By: Relevance
“…Furthermore, a recent report has described the specific induction of two major haploinsufficiency drivers, i.e., RNA splicing alterations and protein destabilization (Fig. 8C,D), by HCM‐linked nontruncating MYBPC3 variants [263]. In this scenario, the examination of RNA splicing alterations and protein destabilization as disease‐associated molecular traits provided supporting evidence of pathogenicity for 11% of nontruncating MYBPC3 VUS in the ClinVar database [263].…”
Section: Hcm‐causing Mybpc3 Variantsmentioning
confidence: 71%
See 1 more Smart Citation
“…Furthermore, a recent report has described the specific induction of two major haploinsufficiency drivers, i.e., RNA splicing alterations and protein destabilization (Fig. 8C,D), by HCM‐linked nontruncating MYBPC3 variants [263]. In this scenario, the examination of RNA splicing alterations and protein destabilization as disease‐associated molecular traits provided supporting evidence of pathogenicity for 11% of nontruncating MYBPC3 VUS in the ClinVar database [263].…”
Section: Hcm‐causing Mybpc3 Variantsmentioning
confidence: 71%
“…8C,D), by HCM‐linked nontruncating MYBPC3 variants [263]. In this scenario, the examination of RNA splicing alterations and protein destabilization as disease‐associated molecular traits provided supporting evidence of pathogenicity for 11% of nontruncating MYBPC3 VUS in the ClinVar database [263]. The disease mechanisms of these two haploinsufficiency drivers in the context of nontruncating MYBPC3 variants are described in the following subsections.…”
Section: Hcm‐causing Mybpc3 Variantsmentioning
confidence: 99%
“…More recently, nanomechanical alterations in mutant cardiac MyBP-C that cause hypertrophic cardiomyopathy have been detected. These alterations occur in the absence of other pathogenic molecular phenotypes (Suay-Corredera et al 2021a;Suay-Corredera et al 2021b). A decrease in mechanical stability at low forces was detected for mutant R495W, which could reduce the braking force exerted by mutant MyBP-C on actomyosin gliding.…”
Section: Muscle Proteinsmentioning
confidence: 93%
“…Although HCM-linked missense (non-truncating) mutations in MYBPC3 are associated with more benign outcomes, functional and structural investigations of a subset of missense mutations reported disturbed cMyBPC architecture and protein–protein interactions [ 53 ] suggesting a protein poison peptide as a potential pathomechanism. However, recent have studies reported RNA splicing defects, resulting from premature stop codon, and protein destabilization cause protein haploinsufficiency in MYBPC3 missense mutations [ 54 , 55 ].…”
Section: Cardiomyopathy Causative Mutations In Sarcomeric Proteinsmentioning
confidence: 99%
“…Another mechanism through which haploinsufficiency contributes to contractile disfunction is the perturbed dynamic myosin conformations. Recent studies using mice models demonstrated that cMyBPC deficiency enhances the myosin state that enables ATP hydrolysis and thin filament interactions (DRX) and reduces the super relaxed conformation associated with low energy consumption (SRX) [ 54 ].…”
Section: Cardiomyopathy Causative Mutations In Sarcomeric Proteinsmentioning
confidence: 99%